Provoca/acciones urbanas. Tácticas ascendentes y creativas en el Centro Histórico de Córdoba, Argentina - Stang, José Ignacio (2018)
The irruption and deployment of a kind of creative artistic actions in and with the urban public space of the Historic Center of the city of Cordoba, Argentina at present are explored and analyzed. Developed by social agents belonging to the field of creative economies, the practices investigated constitute a set of actions that entail a transitory and ephemeral character and that allow, in addition, the possibility of carrying out an integrated reading respect to the instabilities in contemporary city